3D morphometry of red blood cells by digital holography. Issue 12 (19th September 2014) - Memmolo, Pasquale; Miccio, Lisa; Merola, Francesco; Gennari, Oriella; Netti, Paolo Antonio; Ferraro, Pietro
Abstract Three dimensional (3D) morphometric analysis of flowing and not‐adherent cells is an important aspect for diagnostic purposes. However, diagnostics tools need to be quantitative, label‐free and, as much as possible, accurate. Recently, a simple holographic approach, based on shape from silhouette algorithm, has been demonstrated for accurate calculation of cells biovolume and displaying their 3D shapes. Such approach has been adopted in combination with holographic optical tweezers and successfully applied to cells with convex shape. Nevertheless, unfortunately, the method fails in case of specimen with concave surfaces. Here, we propose an effective approach to achieve correct 3D shape measurement that can be extended in case of cells having concave surfaces, thus overcoming the limit of the previous technique. We prove the new procedure for healthy red blood cells (RBCs) (i.e., discocytes) having a concave surface in their central region. Comparative analysis of experimental results with a theoretical 3D geometrical model of RBC is discussed in order to evaluate accuracy of the proposed approach. Finally, we show that the method can be also useful to classify, in terms of morphology, different varieties of RBCs. © 2014 International Society for Advancement of Cytometry